2017
DOI: 10.1002/aelm.201700294
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of High Temperatures on the Switching Kinetics of Redox‐Based Resistive Switching Cells using a High‐Speed Nanoheater

Abstract: Ionic transport greatly influences the switching kinetics of filamentary resistive switching memories and depends strongly on temperature and electric fields. To separate the impact of both parameters on the switching kinetics and to further deepen the understanding of the influence of local Joule heating, a nanometer‐sized heating structure is employed. It consists of a 100 nm wide Pt electrode which, due to Joule heating, serves as heating source upon an electrical stimulus. These self‐heating properties are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 63 publications
(69 reference statements)
2
35
0
Order By: Relevance
“…[1] Several unique structures have been used to evaluate the local temperature in resistive memory devices, [196][197][198] and ultrafast transient electrical measurements were proposed to study an effective device temperature. Understanding heat and energy dissipation is crucial for the evaluation and design of devices (see also Section 4: simulation of RS), since most proposed switching mechanisms rely on thermally activated processes such as defect generation, ionic transport, etc.…”
Section: Switching Mechanismmentioning
confidence: 99%
“…[1] Several unique structures have been used to evaluate the local temperature in resistive memory devices, [196][197][198] and ultrafast transient electrical measurements were proposed to study an effective device temperature. Understanding heat and energy dissipation is crucial for the evaluation and design of devices (see also Section 4: simulation of RS), since most proposed switching mechanisms rely on thermally activated processes such as defect generation, ionic transport, etc.…”
Section: Switching Mechanismmentioning
confidence: 99%
“…For example, it has been demonstrated that the non-linearity of the switching kinetics in lamentary switching VCM cells originates from the temperatureaccelerated dri of the ionic defects. [21][22][23][24][25][26] In AgI-based ECM cells, the strong nonlinearity of the switching kinetics results from the nucleation of the conducting lament at the inert electrode at low voltages, the redox reactions at the metal/insulator interfaces at intermediate voltages and ion migration at very high voltages. 27 Also for other ECM systems these processes have been identied as rate-limiting.…”
Section: Analytical Analysismentioning
confidence: 99%
“…[20][21][22] Higher local temperatures will lead to faster switching speed. According to eqn (19), the value of the effective thermal resistance is the design parameter of choice.…”
mentioning
confidence: 99%
“…This small current, however, increases the local temperature, which in turn increases the electrical conductivity. This results in a thermal runaway leading to an abrupt SET transition 19,20 . During the RESET Joule heating also occurs, and the oxygen vacancies drift away from the active electrode (high work function metal).…”
mentioning
confidence: 99%